Grace Roberts: capstone - Roberts, Grace, artist (Colorado State University. Libraries, 2025)
The artist's statement: My work is informed by probing the frameworks of function, ornament, and architecture. Function is an expansive term, whether it is a vessel that brings sustenance to your mouth, or a story that keeps you moving through life. My pieces are created to be used for eating and drinking. Their function is to tell stories: to invite stories to be discovered. They are created to raise curiosity in their patrons. In the search for the bounds of function, architecture became a theme in my pots. Walking through the world, I tend to compare the buildings we live in to the things we eat off of. On the surface level, there is the connection that they are both basic necessities for sustaining life, and naturally, the oldest art forms. There is a clear connection between beauty and human survival that is indubitably tied to functional pottery and always has been. The comparison between the two art forms began to beg questions: Why do humans spend precious time and resources on ornament? Is to live beautifully a condition of our persistence? These questions remain unanswered, but frequently explored in my work. Tiles beautifully exemplify the one in the many. A mosaic is a way to take the discarded and give them a completely new life. My tiled pieces use glaze scraps that would otherwise be thrown out. Empowering a beautiful color palette of chance to come to fruition – allowing a serendipitous aesthetic to be born. Adding architectural language in my work is a way to explore the way in which ceramic materials are ingrained in the function of our world. My thought process goes something like this: If you drink from a ceramic vessel, and you know it is ceramic, what assertions might you draw from this paradigm? By adding tiles to my wares, there is a connection that the viewer makes to the presence of ceramics (intimate and expansive) in their everyday life. The experience of drinking from this vessel is the gateway into seeing more: from the ground we walk on, to the walls of our home.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: pottery